Changes in vitellogenin expression caused by nematodal and fungal infections in insects - Kodrík, Dalibor; Ibrahim, Emad; Gautam, Umesh K; Čapková Frydrychová, Radmila; Bednářová, Andrea; Krištůfek, Václav; Jedlička, Pavel (Journal of experimental biology, 2019)
This study examined the expression and role of vitellogenin (Vg) in the body of the firebug Pyrrhocoris apterus (Heteroptera, Insecta) during infection elicited by two entomopathogenic organisms, the nematode Steinernema carpocapsae and the fungus Isaria fumosorosea Infection by S. carpocapsae significantly upregulated Vg mRNA expression in the male body. The corresponding increase in Vg protein expression was also confirmed by electrophoretic and immunoblotting analyses. Remarkably, in females, the opposite tendency was noted. Nematodal infection significantly reduced both Vg mRNA and Vg protein expression levels in fat body and hemolymph, respectively. We speculate that infection of reproductive females reduces Vg expression to a level that is still sufficient for defense, but is insufficient for reproduction. This circumstance reduces energy expenditure and helps the individual to cope with the infection. Importantly, purified Vg significantly inhibited growth of Xenorhabdus spp., an entomotoxic bacteria isolated from S. carpocapsae. However, the effect of Vg against I. fumosorosea was not so obvious. The fungus significantly stimulated Vg gene expression in males; however, a similar increase was not recapitulated at the protein level. Nevertheless, in females, both mRNA and protein Vg levels were significantly reduced after the fungal infection. The obtained data demonstrate that Vg is probably an important defense protein, possibly with a specific activity. This considerably expands the known spectrum of Vg functions, as its primary role was thought to be limited to regulating egg development in the female body.
Keywords: Animals; Hypocreales; Female; ženské pohlaví; Rhabditida; vitelogeniny; Host-Parasite Interactions; interakce hostitele a parazita; hmyzí proteiny; Male; interakce hostitele a patogenu; exprese genu; Insect Proteins; zvířata; mužské pohlaví; Host-Pathogen Interactions; Vitellogenins; Gene Expression; Heteroptera